ANALISIS POTENSI DAN EFEKTIVITAS PENERIMAAN PAJAK RESTORAN DI KOTA TOMOHON - Makalew, Maria Debora; Nangoi, Grace B.; Lambey, Robert (Universitas Sam Ratulangi, 2018)
Â Â Â Â Â Â Â Â Â Â Â Restaurant tax is one of the solutions to increase local revenues, since one of the regionâ€™s largest indigenous revenues is contributed by taxes in the City of Tomohon. The purpose of this research is to know the potential and effectiveness of restaurant tax in Tomohon City. The result showed that the realization of restaurant tax obtained exceeds the target of restaurant tax that has been set but the target tax restaurant has a very far difference from the potential tax restaurant. This is evidenced by the calculation of the difference between the target of restaurant tax receipts to the potential of restaurant tax revenues. The level of tax effectiveness of Tomohon City restaurant is fiscal year 2013-2016 is considered â€œvery effectiveâ€. It can be seen from the realization of tax revenue every year that exceeds the target of tax revenue. The result of the research can be concluded that, the tax revenue of restaurants in Tomohon City has been very effective but it does not reflect the actual potential, therefor the Regional Finance Agency of Tomohon should optimize the income of restaurant tax in order to increase the local revenue.Keywords : Restaurant Tax, Admission Potential, Effectiveness